SOME OBSERVATIONS ON THE INTRACELLULAR LOCALIZATION OF THE VIRUS OF HERPES SIMPLEX IN THE CHICK EMBRYO LIVER - Gray, Alan (The Rockefeller University Press, 1954)
The growth cycle of the virus of herpes simplex in chick embryo liver has been shown to follow the same pattern as in the chorioallantoic membrane and the rabbit's corneal cells. However, there is considerable variability in the time taken for the yolk sac-inoculated virus to get from the yolk sac into the liver. A brief description has been given of various fractionation procedures employed for obtaining isolated nuclei. It has been shown that free virus is not selectively adsorbed to isolated nuclei. Evidence has been presented to show that in the herpes-infected chick embryo liver, large proportions of the total virus can at times be found associated with the nuclear fraction. The percentage of the total virus in the nuclear fraction varies inversely with the titer of virus in the whole liver, and the number of hours after inoculation of the virus; only a negligible amount (as compared with that in the total) being associated with the nuclear fraction when a period of over 12 hours has elapsed after reappearance of virus. Furthermore, demonstration of virus in the isolated nuclei following extraction with hypertonic NaCl provides additional evidence that this virus is intimately associated with the nuclei.